Subclinical joint inflammation in patients with psoriasis without concomitant psoriatic arthritis: a cross-sectional and longitudinal analysis. Issue 12 (25th February 2016) - Faustini, Francesca; Simon, David; Oliveira, Isabelle; Kleyer, Arnd; Haschka, Judith; Englbrecht, Matthias; Cavalcante, Alan Rodrigues; Kraus, Sebastian; Tabosa, Taiane Ponte; Figueiredo, Camille; Hueber, Axel J; Kocijan, Roland; et al.
Abstract : Objectives: To search for subclinical inflammatory joint disease in patients with psoriasis without psoriatic arthritis (PsA), and to determine whether such changes are associated with the later development of PsA. Methods: Eighty-five subjects without arthritis (55 with psoriasis and 30 healthy controls) received high field MRI of the hand. MRI scans were scored for synovitis, osteitis, tenosynovitis and periarticular inflammation according to the PsAMRIS method. Patients with psoriasis additionally received complete clinical investigation, high-resolution peripheral quantitative CT for detecting erosions and enthesiophytes and were followed up for at least 1 year for the development of PsA. Results: 47% of patients with psoriasis showed at least one inflammatory lesion on MRI. Synovitis was the most prevalent inflammatory lesion (38%), while osteitis (11%), tenosynovitis (4%) and periarticular inflammation (4%) were less frequent. The mean (±SD) PsAMRIS synovitis score was 3.0±2.5 units. Enthesiophytes and bone erosions were not different between patients with psoriasis with or without inflammatory MRI changes. The risk for developing PsA was as high as 60% if patients had subclinical synovitis and symptoms related to arthralgia, but only 13% if patients had normal MRIs and did not report arthralgia. Conclusions: Prevalence of subclinical inflammatory lesions is high in patients with cutaneous psoriasis. Arthralgia in conjunction with MRI synovitis constitutes a high-risk constellation for the development of PsA.